pH- and thermosensitive nano(ferro)gels based on N-isopropylacrylamide and acrylic acid - Samchenko, Yu.M.; Kernosenko, L.O.; Kryklya, S.O.; Pasmurtseva, N.O.; Poltoratska, T.P.; Marynin, A.I. (Reports of the National Academy of Sciences of Ukraine, 2017)
Nanosized hydrogels based on thermosensitive poly-N-isopropylacrylamide, copolymers with acrylic acid, and their nanocomposites with incorporated magnetite nanoparticles (approximate particle size of 100-200 nm) are synthesized. It was shown that the hydrogel matrix size and the zeta potential of nanoparticles depend on the temperature and pH. The diameter of nanoparticles is reduced by 2-3 times, if the hydrogel is heated up to 32 °C, and by 3-5 times, if pH decreases below 5. This creates conditions for the controllable release of incorporated anticancer drugs (in particular, doxorubicin) and for using nanogels in therapeutic hypothermia. Incorporation of nanosized magnetite into the hydrogel matrices provides a controlled localization of therapeutic systems in close proximity to target organs by applying a low-intensity constant magnetic field.